2019
DOI: 10.1186/s13690-019-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Talking health: trusted health messengers and effective ways of delivering health messages for rural mothers in Southwest Ethiopia

Abstract: Summary Background Access to trusted health information has contribution to improve maternal and child health outcomes. However, limited research to date has explored the perceptions of communities regarding credible messenger and messaging in rural Ethiopia. Therefore, this study aimed to explore sources of trusted maternal health information and preferences for the mode of delivery of health information in Jimma Zone, Ethiopia; to inform safe motherhood implementation research proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…-Isaac This failure to address 'root causes' reflects how the HEW role has come to be seen by others working in the Ethiopian health system, and by community members themselves. Study participants noted that HEWs were most respected for providing clinical services (such as injections and medications), although a large part of their mandate and training is around health education, as corroborated by previous findings from our research [42]. Such education initiatives, however, are thought to be less valued by the community.…”
Section: Improving Access To Women's Health Services At the Communitysupporting
confidence: 84%
See 1 more Smart Citation
“…-Isaac This failure to address 'root causes' reflects how the HEW role has come to be seen by others working in the Ethiopian health system, and by community members themselves. Study participants noted that HEWs were most respected for providing clinical services (such as injections and medications), although a large part of their mandate and training is around health education, as corroborated by previous findings from our research [42]. Such education initiatives, however, are thought to be less valued by the community.…”
Section: Improving Access To Women's Health Services At the Communitysupporting
confidence: 84%
“…This research is part of the Safe Motherhood Project, a mixed-methods intervention trial testing the rollout and scale up of interventions to reduce preventable maternal and newborn morbidity and mortality [41][42][43]. The Safe Motherhood Project has rolled out two interventions (an information, education and communication intervention, and maternity waiting area (MWA) upgrades) and conducted multiple rounds of data collection (prior to the design of the interventions, at baseline and at end line) [44].…”
Section: Study Approach and Designmentioning
confidence: 99%
“…These improvements, in turn, rest partly on subnational health managers' perspectives on health equity and how they can act to improve it. We are unaware of prior research probing this specific aspect of subnational health system responsibilities, hence undertook the study reported on in this article, as part of a larger implementation study [35][36][37].…”
Section: Perceptions Of Health Equity In Ethiopiamentioning
confidence: 99%
“…21 Utilizing extension officers as agents for sharing information on antenatal supplements has been recommended, 21 and continued support of the program could leverage their home visits and trusted relationships to follow-up on supplementation. 57 As in formative research, 21 counseling on supplements for prevention and as a dietary supplement led to increased motivation and clarified need for concurrent use of IFA for "low blood" and calcium for "high blood." In light of expected low adherence to complex supplementation regimens requiring women to take pills 3 to 4 times a day, we anticipated that a reduced supplementation schedule would be easier to adhere to, such that calcium consumption might be equivalent.…”
Section: Discussionmentioning
confidence: 99%